3D Prediction of the Wake Rotor of Horizontal Axis Wind Turbines - Belkheir, Noura; Dobrev, Ivan; Sofiane, khelladi (International Journal of Engineering and Technology, 2018)
The investigation of the wake development of the wind turbines is important for the wind turbine design, in this paper a modeling of a complete rotor of three blades was implemented to investigate the wake downstream of a wind turbine with horizontal axis. The rotor modeled studied here is a commercial wind turbine i.e. Rutland 503 of the Marlec Company.The numerical simulations are made for many different tip speed ratio, these are chosen in reference to experimental work realized in the laboratory of ENSAM. The Numerical results were obtained, using the approach Reynolds Averaged Navier Stokes (URANS) equations, the turbulence model used is the Shear Stress Transport (SST) kâ€“Ï‰.The solutions are obtained by using the package FLuent solver, who uses finite volume method. The wake characteristics of the rotor are compared with the experimental data. The results presented the development of the downstream wake of the wind turbine rotor.These results provide a good understanding of the unsteady flow in a wind turbine, which will be used to better optimize wind turbine structures and increase the number of wind turbines in wind farms.Â